The Influence of Work-Life Balance on Psychological Well-Being Moderated by Satisfaction with Coworkers in Gen Z Employees in Startup Companies in Padang City - Elisabeth Angelina Zega; Mega Asri Zona (International Journal of Economics and Management Research, 2024)
Work-life balance is an individual's ability to manage time, energy, and attention between work and personal life proportionally. This study aims to analyze the effect of work-life balance on psychological well-being in Gen Z employees at startup companies in Padang City, as well as to examine the moderating role of satisfaction with coworkers in the relationship. This study uses a quantitative approach with a causal design. The sample consisted of 130 respondents selected through purposive sampling techniques. Data were collected through a Google Forms-based questionnaire and analyzed using the Moderated Regression Analysis (MRA) technique with the help of SPSS software. The results showed that work-life balance had a positive and significant effect on psychological well-being. This means that the better the balance of life felt by employees, the higher their level of psychological well-being. In addition, satisfaction with coworkers has been shown to positively moderate the relationship. Employees who have good relationships with coworkers feel greater benefits of work-life balance on their psychological well-being. This study is supported by the Affective Events Theory (AET), which explains that events in the work environment, such as social interactions and emotional experiences, can shape psychological responses and affect individual well-being. These findings contribute to human resource management in creating work strategies that support life balance and strengthen relationships between employees, especially in startup work environments.